On diameters estimations of the commuting graphs of Sylow p-subgroups of the symmetric groups - Leshchenko, Yu.Yu.; Zoria, L.V. (Carpathian Mathematical Publications, 2013)
The commuting graph of a group G is an undirected graph whose vertices are non-central elements of G and two distinct vertices x,y are adjacent if and only if xy=yx. This article deals with the properties of the commuting graphs of Sylow p-subgroups of the symmetric groups. We define conditions of connectedness of respective graphs and give estimations of the diameters if graph is connected.